Analysis of Factors Influencing Repurchase Decision of Flight Tickets of Garuda Indonesia Airlines Using Binary Logistic Regression - Rizki Agung Ramadani; Tiyanda Hanti Arum Kusuma; Rinta Agustiani Dwiputri; Jerry Heikal (Universitas KH. Abdul Chalim Mojokerto, 2025)
The aviation industry in Indonesia is one of the sectors that has experienced rapid growth along with the increasing mobility of society and the need for air transportation. This study aims to analyze the factors that influence the decision to repurchase airline tickets at Garuda Indonesia Airlines using the Binary Logistic Regression method. The aviation industry in Indonesia, especially Garuda Indonesia Airlines, faces a major challenge in maintaining customer loyalty amidst tight market competition. Consumer decisions to repurchase airline tickets or make a repurchase are important indicators in determining the success of an airline's marketing and service strategy. This study uses a quantitative approach with a cross-sectional survey design, involving 197 respondents selected through a purposive sampling technique. Data were collected through a structured questionnaire that measured seven factors of service quality and customer satisfaction. The analysis was conducted using SPSS, and the results showed that of the various indicators tested, four factors had a significant influence on repurchase decisions. These factors are call center services, promotions through official websites, email blasting, and Garudamiles services. Call center service factors, promotions through websites and email blasting, and the existence of Garudamiles membership products tend to be important factors that influence repurchase decisions with an accuracy rate of 80.7%. These results provide insight for Garuda Indonesia to optimize marketing strategies to increase customer retention and profitability.